(untitled) (Asian Journal of Medical and Biological Research, 2017)
The study was made on testing purity of different marketed brands of three insecticide groups such as quinalphos, malathion and fenitrotion in the Pesticide Analytical Laboratory under Division of Entomology, Bangladesh Agricultural Research Institute (BARI), Gazipur using suitable protocols GC-FID. Nineteen marketed brands of these insecticides collected form dealers or retailers of Jessore, Gazipur and Rangpur region were analyzed and estimated their purity in two seasons of 2006-2007 and 2007-2008. In these two seasons, among five marketed brands of Malathion, only one brand (MTF) had 98.95-100% purity which was collected from Jessore in 2007-08 and Gazipur in both the seasons and considered to be standard or acceptable product, but in other regions, this brand contained less AI and was found to be <95% pure which was considered as substandard product. The remaining brands contained 22-92% purity including SRL and MTX having small amount of AI (22-44% purity) and all these were unacceptable and impure. Fenitrothion with five marketed brands showed ? 96% purity only in SMT brand in Gazipur and Jessore in 2006-07 and in all the three locations in 2007-08 seasons and this brand considered as standard product. The other four brands of this insecticide had purity at substandard level in all locations in two seasons. Quinalphos with 8 marketed brands, only MLX in 2006-07 and BLX in 2007-08 seasons in all locations had ? 95 % purity which was standard product. ALX and CRX in 2006-07 were almost similar and close to MLX except one location, CRX in Gazipur and ALX in Jessore but these two brands were substandard and impure (65-86%) in next season in all locations. The other brands (KNX, QNP, VNR and SLX) were also substandard and impure having 59% to 87% purity. Asian J. Med. Biol. Res. December 2016, 2(4): 616-623